Posisi Evaluasi Diri dalam Sistem Penjaminan Mutu Pendidikan Tinggi - Luqman, Asaduddin (IAIN Ponorogo, 2017)
Self-evaluation serves as a milestone of a development, where suchdevelopment deals withthe planned change. Therefore, it is essential to understand how to conduct self-evaluation in comprehensive, well-structured, and systematicwaysinwhichthe results can be used as a basis in the planning process in order to achieve suchquality improvement sustainably. The analyses conductedinvolve strength, weakness,opportunity, and treats (SWOT analysis). By knowing the pre-existing weaknesses,efforts can be done to minimize the weaknesses by utilizing the owned strengths.Similarly, by understanding the possible challenges that may be faced in advance,thechallenges can be overcome with utilizing every single of opportunities, so that thechallenge can be a motivation for all managers in improving the quality of the institution.Self-evaluation can be carried out following five procedures as follows: preparation andplanning, structuring organizational work, implementation of self-evaluation, use ofpeer experts and follow-up. The implementation of good self-evaluation activities can beseen with several attributes, concerning the process of self-evaluation organizationandself-evaluation report.Ø¥Ù ØªÙÙÙÙ Ø§ÙØ°Ø§Øª Ù ÙØ·ÙÙ ÙÙØªØ¯ ÙÙØªØ·ÙÙØ± ÙØ§ÙØªÙÙ ÙØ©Ø ØÙØ« Ø£Ù Ø§ÙØªØ·ÙÙØ± ÙÙ Ø§ÙØªØºÙÙØ± Ø§ÙÙ Ø¨Ø±Ù Ø¬. Ø¨ÙØ°Ø§ ÙÙØªØ§Ø¬Ø¥ÙÙ Ø£Ù ÙÙÙÙ ØªÙÙÙÙ Ø§ÙØ°Ø§Øª ÙÙÙ Ø§ Ø´Ø§Ù ÙØ§ Ù Ø±ÙØ¨ÙØ§ ÙÙ ÙØ¸ÙÙ Ø§ ØØªÙ ØªÙÙÙ Ø§ÙÙØªØ§Ø¦Ø¬ Ù ÙÙ ÙÙ ÙÙ Ø£Ù ØªØ³ØªØ®Ø¯Ù ÙØ£Ø³Ø³ ÙÙ Ø¹Ù ÙÙØ©Ø§ÙØªØ®Ø·ÙØ· ÙÙØØµÙÙ Ø¹ÙÙ ØªØ±ÙÙØ© Ø§ÙØ¬ÙØ¯Ø© Ù ØªÙØ§ØµÙØ§ Ù Ø³ØªÙ Ø±ÙØ§. ÙØ´Ù Ù Ø§ÙØªØÙÙÙ Ø¹ÙÙ ÙÙØ§Ø· Ø§ÙÙÙØ©Ø ÙÙØ§Ø· Ø§ÙØ¶Ø¹ÙØ ÙØ§ÙÙØ±ØµÙØ§ÙØ§Ù ÙØ§ÙÙÙØ§ØªØ ÙØ§ÙØªÙØ¯ÙØ¯Ø§Øª. ÙØ¨Ù Ø¹Ø±ÙØ© ÙÙØ§Ø· Ø§ÙØ¶Ø¹Ù ÙÙÙ ÙÙ Ø§ÙÙÙØ§Ù Ø¨Ø§ÙÙ ØØ§ÙÙØ§Øª ÙØªÙØµÙØ±ÙØ§ Ø¨Ø§Ø³ØªÙØ§Ø¯Ø© ÙÙØ§Ø· Ø§ÙÙÙØ©Ø§ÙÙ ÙØ¬ÙØ¯Ø©. ÙÙØ°Ø§ Ø¨Ù Ø¹Ø±ÙØ© Ø§ÙØªØØ¯ÙÙØ§Øª Ø§ÙØªÙ ÙØ§Ø¨Ø¯ Ù Ù Ù ÙØ§Ø¬ÙØªÙØ§Ø ÙØ¨ÙØ¬ÙØ¯ Ø§ÙÙØ±Øµ ÙØ§ÙØ§Ù ÙØ§ÙÙØ§Øª ÙÙØ±Ø¬Ù Ø£Ù ØªÙÙØ§Ø¬ÙÙØ°Ù Ø§ÙØªØØ¯ÙÙØ§Øª Ø¨ÙØ§ ØØªÙ ØªÙÙÙ ÙØ°Ù Ø§ÙØªØØ¯ÙØ§Øª Ø¯ÙØ§ÙØ¹ ÙØ¬Ù ÙØ¹ Ø§ÙÙ Ø³Ø¤ÙÙÙÙ ÙØªØ±ÙÙØ© Ø¬ÙØ¯Ø© Ø§ÙÙ ÙØ¸Ù Ø©. ÙØ¥Ù Ø§ÙÙÙØ§Ù Ø¨ØªÙÙÙÙ Ø§ÙØ°Ø§Øª ÙØªÙ Ø¹Ù Ø®Ù Ø³ Ù Ø±Ø§ØÙ ÙÙÙ : Ù Ø±ØÙØ© Ø§ÙØ§Ø³ØªØ¹Ø¯Ø§Ø¯ ÙØ§ÙØªØ®Ø·ÙØ·Ø ÙÙ Ø±ØÙØ© ØªÙØ³ÙÙ Ø§ÙØ¹Ù ÙØ ÙÙ Ø±ØÙØ©ØªÙÙÙØ° ØªÙÙÙÙ Ø§ÙØ°Ø§ØªØ ÙÙ Ø±ØÙØ© Ø§Ø³ØªÙØ§Ø¯Ø© Ø§ÙØ£ØµØØ§Ø¨ Ø§ÙØ®Ø¨Ø±Ø§Ø¡ Ø«Ù Ø§Ø³ØªÙ Ø±Ø§Ø±ÙØ© Ø§ÙØ¹Ù Ù. ÙØªØ·Ø¨ÙÙ ØªÙÙÙÙ Ø§ÙØ°Ø§Øª Ø§ÙØ¬ÙÙØ¯ ÙÙ ÙÙÙ Ø¹Ø±ÙØªÙ Ø¨Ø§ÙÙ Ø¤Ø´ÙØ±Ø§Øª Ø§ÙÙ ØªØ¹ÙÙØ© Ø¨Ø¹Ù ÙÙØ© ØªØ·Ø¨ÙÙ ØªÙÙÙÙ Ø§ÙØ°Ø§Øª ÙÙØªØ§Ø¨Ø© Ø§ÙØªÙØ±ÙØ± ÙÙØ°Ø§ Ø§ÙØªØ·Ø¨ÙÙ.